Social relevance of the Early Childhood Education Degree program at the Mariana de Pasto University. - Velasco Guerrero , María Mercedes (SATHIRI, 2023)
e purpose of this research was to describe the social relevance of the Bachelor’s Degree in Early Childhood Education at the Mariana University, Pasto, Colombia. To achieve this, a qualitative study was developed with a documentary review design in three phases: preparatory, descriptive and interpretive. The results indicated that the greatest number of strengths occurs in terms of the needs of students and the local government, while the greatest number of opportunities for improvement occurs in terms of the needs of the national government and the international community. It was concluded that the credit system, program contents, professional practices and the self-assessment system are strengths; These are opportunities to improve national and international student and teacher mobility, as well as the restructuring and development of research that already exists within the program.